The Urgency of Entrepreneurship Education - Puspayanti, Amalia; I Made Sutajaya (Widyadewata, 2024)
This research is a literature study which aims to describe urgency of entrepreneurship education. Based on the results of the literature review, it can be described that entrepreneurship education is fundamental to support survival based on needs and strengths. Entrepreneurship education will instill three main characters, namely critical thinking, creative and innovative. Implementation of entrepreneurship education is the same as the process of instilling character in students. Strategies that can be implemented are: (1) integrating intra-curricular, co-curricular and extra-curricular learning; (2) literacy activities that invite business practitioners (if possible, some from alumni) as guest speakers; (3) make visits to business locations; (4) carrying out internships in business units; and (5) forming business units in schools/madrasah.